2016
DOI: 10.1177/0007650316645051
|View full text |Cite
|
Sign up to set email alerts
|

A Nonprofit Perspective on Business–Nonprofit Partnerships: Extending the Symbiotic Sustainability Model

Abstract: Using the symbiotic sustainability model as a framework, this research investigates how many and with which businesses top nonprofit organizations report partnerships. We examined the websites of the 122 largest, most recognizable U.S. nonprofits. These websites included information about 2,418 business-nonprofit (B2N) partnerships with 1,707 unique businesses. The results suggest key differences with previous research on how U.S. Fortune 500 companies report B2N partnerships. Leading nonprofits report more B2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 72 publications
0
56
1
Order By: Relevance
“…Similarly to what was underlined in [5], this situation has created a sort of 'restitution' of the growth enjoyed by the firm, thanks to knowledge sharing and relationship creation experienced in the former two BM evolution steps. This restitution offers a win-win situation, as Perpetua endorses the different projects yet also gains further development from them in a virtuous circle of synergistic value creation [7,16] and formation of symbiotic SBMs [52,53]. The described evolution of Alisea through the three BMs appears to be the product of multiple interactions created within business-to-business and cross-sector collaborations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly to what was underlined in [5], this situation has created a sort of 'restitution' of the growth enjoyed by the firm, thanks to knowledge sharing and relationship creation experienced in the former two BM evolution steps. This restitution offers a win-win situation, as Perpetua endorses the different projects yet also gains further development from them in a virtuous circle of synergistic value creation [7,16] and formation of symbiotic SBMs [52,53]. The described evolution of Alisea through the three BMs appears to be the product of multiple interactions created within business-to-business and cross-sector collaborations.…”
Section: Discussionmentioning
confidence: 95%
“…The network level of analysis in collaborations has been less studied in the cross-sector [50] and business network literature [51], where the point of view is often that of the focal organisation. Partnerships and collaborations are the relevant intermediate objects of study, located between single organisations and society, and identified by means of an institutionalisation process communicatively co-constructed by partners and stakeholders also toward symbiotic SBMs [52,53]. Further, interaction between partners can restructure their BMs through collaboration or even determine the creation of a completely new BM [54]; to facilitate this interaction, the eco-innovation literature has underlined the crucial role of intermediaries in supporting firms in the innovation process [55].…”
Section: The Firm and Its Network: Business And Cross-sector Collabormentioning
confidence: 99%
“…NPOs are benefiting from this increasing corporate concern and have been diversifying their funding sources (Baur and Schmitz 2012), especially with the business industry. In this sense, NPOs rarely maintain exclusivity with just one company as their sponsor (Shumate et al 2018). In the context of raising uncertainty and economic constraints that may inhibit corporations from offering donations to non-profit organisations and reduce the level of philanthropic contributions (Dunn 2004), as well as the increasing competition for grants within the third sector, a diversified mix of funding sources has increasingly been considered a prudent strategy to reduce unpredictability, and also to show competency, to grow in economic value, and to be recognised as having managerial merit (Shumate et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, NPOs rarely maintain exclusivity with just one company as their sponsor (Shumate et al 2018). In the context of raising uncertainty and economic constraints that may inhibit corporations from offering donations to non-profit organisations and reduce the level of philanthropic contributions (Dunn 2004), as well as the increasing competition for grants within the third sector, a diversified mix of funding sources has increasingly been considered a prudent strategy to reduce unpredictability, and also to show competency, to grow in economic value, and to be recognised as having managerial merit (Shumate et al 2018). Raising new donations is directly related to improvements in the financial performance and sustainability of NPOs (Ferreira et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The research on cross-sector partnerships, i.e., alliances in which firms, governments, and civil society actors cooperate to address social and environmental causes, has received a great amount of attention during the last few decades [1][2][3][4][5][6][7]. The increasingly complex problems these partnerships address, their implications for sustainable development, and the ethical dilemmas that characterize the interactions among the three sectors suggest its growing relevance for both practitioners and scholars from various academic disciplines, including sustainability.…”
Section: Introductionmentioning
confidence: 99%